GE_GERICHTE C/11199/2021 vom 12. Dezember 2023 - GE Cour de justice (2023)
ACTION EN PAIEMENT D'ENTRETIEN;GARDE ALTERNÉE;RELATIONS PERSONNELLES;CURATELLE;OBLIGATION D'ENTRETIEN;ENFANT | CC.308; cc.276; CC.285; CC.307; CC.296; CC.273.al1; CPC.316.al3